Yield performance stability of adapted and improved cowpea in the Equatoria region of South Sudan - Ngalamu, T.; Meseka, S.; Galla, J.O.; Tongun, N.J.; Ochanda, N.W.; Ofori, K. (Agricultural Research Communication Center, 2019)
Cowpea is an important food crop with high nutritional and socio-economical values in South Sudan. However, the lack of improved varieties is one of the main production constraints. This study was undertaken to assess the yield stability performance of improved cowpea genotypes across six environments in South Sudan in 2014 and 2015. Nine genotypes were evaluated in a randomized complete block design with three replications. Genotype and genotype x environment biplot analysis method was used to determine yield stability. Highly significant (p< 0.001) genotype x environment interaction effect was detected for seed yield. IT90K-277-2 had the highest while ACC004 had the lowest grain yield. Palotaka was as highly discriminating and repeatable environment compare to the other testing sites. IT07K-211-1-8 and Mading Bor II were the most responsive genotypes, while IT90K-277-2 was the most stable high yielding genotype across the test environments and can be grown by farmers across the region.